Elizabeth Price - Lingwood, James 1959- (Artangel, 2019)
The first major publication on Elizabeth Price's work, 'SLOW DANS' centres on a trilogy of new multi-channel works: KOHL, FELT TIP and THE TEACHERS, completed by Price over the past few years. The three works respectively present a fictional past, imagined future and parallel present and move from a flooded subterranean location to an executive realm. 'SLOW DANS' draws on recent social and political histories ranging from the systematic abandonment of coal mines, to certain technological and demographic revolutions in office work. Interspersing sections of stills from Price's work, Katrina Palmer's text narrates her rich experience of viewing 'SLOW DANS', Pavel Pys draws parallels between Price's work and baroque trompe l'oeil painting, and Adrian Rifkin considers Price's work in a world saturated with archives and images. Mary Griffiths' glossary provides backgrounds to a wide range of source materials from mine-head architecture pitheads to men's neckties from the 1970s and 80s
Auf dem Buchrücken: "Elizabeth Price - Slow dans"
'Slow dans' was first exhibited in Elizabeth Price : A Long Memory at the Whitworth, The University of Manchester, 25 October 2019-1 March 2020
Keywords: Price, Elizabeth -- 1966-; Price, Elizabeth / 1966- / Exhibitions; Video art / Great Britain / Exhibitions; Price, Elizabeth / 1966-; Video art; Great Britain; Exhibition catalogs; Ausstellungskatalog -- Whitworth Art Gallery -- 25.10.2019-01.03.2020; Bildband